HYDRODYNAMIC STUDY OF HEAVE COMPENSATED LANDING SYSTEM - HE , DONGHAI (2020)
With the limitation of lowering capacity, traditional lowering systems cannot meet the challenge to lower emerging ultra-large subsea equipment to the seabed. One source affecting the lowering capability of a lowering system is disturbance on the lifting line. In this work, a lowering system, called Heave Compensated Landing System, has been proposed for reducing disturbance on the lifting line by enhancing its heave compensation. However, its hydrodynamic and heave compensated characteristic are poorly understood. To analyze its hydrodynamic characteristic, especially to evaluate its heave compensated performance, this research conducts a case study of this system to lower a 450t manifold. The hydrodynamic characteristic of the Heave Compensated Landing System is investigated using both non-coupled model and fully coupled model and analyzed both in frequency domain and time domain.